Helminths of two species of Bachia, B. dorbignyi (Duméril & Bibron, 1839) and B. bresslaui (Amaral, 1935) (Sauria: Reptilia) - Holanda, Vitoria Hellen (2025)
Bachia is a widespread genus of lizard, endemic to the Neotropical region. Despite this huge distribution, little is known about aspects of their ecology, such as diet and parasitism. Herein, we present data on helminth infection of two species of the genus, B. dorbignyi (Duméril & Bibron, 1839) and B. bresslaui (Amaral, 1935). Th irty-one specimens were analyzed, two helminths were found to B. dorbignyi, cystacanths of Centrorhynchus sp., and the nematode Oswaldocruzia sp. For B. bresslaui, one helminth was found, the cestode Oochoristica sp. Our study provides the first record of parasites infecting B. dorbignyi and B. bresslaui.